Efforts To Protect The Rights Of Suspects Through The Pre-Trial Process In Examinations At The Investigative Level - Muhidin, Muhidin; Puji Rahayu, Anjani; Fatmawati, Ina; Putri, Machelinda; Rifa'atul Lailiah, Melly; Fatmawati, Sri (JURNAL RUANG HUKUM, 2022)
Coercive action by the competent authorities in investigations and prosecutions can be controlled by the courts. The purpose of establishing this facility is so that the rights of suspects can be protected, especially in relation to illegal arrests and detentions as well as termination of investigations and prosecutions. Even though the facility is regulated positively (Article 82 paragraph (1) letter d), in practice there are still deficiencies in its preparation and application in court, so that the human rights of suspects are not protected. This study discusses how pretrial authority protects the rights of suspects in Decision 99/Pid.Pra/2022/PN JKT.SEL and pretrial objectives at the investigative level, what is the role of pretrial as an effort to protect the rights of suspects and pretrial objectives at the investigative level. Therefore the purpose of this study is to determine pretrial authority in an effort to protect the rights of suspects for pretrial purposes at the level of investigation. The purpose of this study is to answer through the application of legal-philosophical methods and library research through theoretical research with legal theory and its relation to law enforcement prosecution in the judiciary. The results of the research prove that power and other powers continue to influence the institutional legal system whose independence is guaranteed by law and justice, especially the influence of pretrial authority on efforts to protect suspects' rights at the pretrial level and objectives at the investigative level. Also the role of the court as a procedural authority is therefore not completely independent. The main task of the judiciary remains to promote peace and justice. Therefore, to instill a sense of peace among justice seekers, it is necessary to strengthen the legal system, which is the last haven for justice seekers.